2012
DOI: 10.4161/cbt.13.4.18691
|View full text |Cite
|
Sign up to set email alerts
|

Thymosin β-4 in colorectal cancer is localized predominantly at the invasion front in tumor cells undergoing epithelial mesenchymal transition

Abstract: Objective: Thymosin b-4 (Tb 4 ) is a ubiquitous peptide that plays pivotal roles in the cytoskeletal system and in cell differentiation during embryogenesis. Recently, a role for Tb 4 has been proposed in experimental and human carcinogenesis. This study was aimed at evaluating the correlation between Tb 4 immunoractivity and colorectal cancer, with particular attemption to tumor cells undergoing epithelial-mesenchymal transition. Methods and Results: 86 intestinal biopsies were retrospectively analyzed includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 41 publications
6
23
0
Order By: Relevance
“…** P < 0.01 versus control SCC-15 cells; ## P < 0.01 compared with control SCC-25 cells strongly increased the invasiveness of OSCCs and induced the activation of MMP-2. This is consistent with a report by Nemolato et al (2012), showing upregulation of Tβ4 expression in invading tumor cells with features of EMT. Tβ4-upregulated colorectal cancer cells are more invasive, and Tβ4-downregulated cells show decreased MMP-2 expression (Piao et al 2014).…”
Section: Discussionsupporting
confidence: 94%
“…** P < 0.01 versus control SCC-15 cells; ## P < 0.01 compared with control SCC-25 cells strongly increased the invasiveness of OSCCs and induced the activation of MMP-2. This is consistent with a report by Nemolato et al (2012), showing upregulation of Tβ4 expression in invading tumor cells with features of EMT. Tβ4-upregulated colorectal cancer cells are more invasive, and Tβ4-downregulated cells show decreased MMP-2 expression (Piao et al 2014).…”
Section: Discussionsupporting
confidence: 94%
“…The previously reported diffuse cytoplasmic immunostaining was substituted by a focal reactivity, mainly represented by a perinuclear spot-like staining pattern highly suggestive of a translocation of Tβ4 from vacuoles towards the trans-Golgi network. A similar cytoplasmic localization of Tβ4 has been previously observed by our group in the human normal colon mucosa, in the proximity of colon cancer [29]. In that study, Tβ4-immunoreactive perinuclear spots were frequently detected in the enterocytes covering the intestinal mucosa in close proximity of colon cancer.…”
Section: Discussionsupporting
confidence: 90%
“…A study investigating Tβ4 expression in a limited number of human colon cancers reported highly variable immunostaining for Tβ4 in tumor cells and in endothelial and stromal cells (10). A recent study from our group showed strong Tβ4 cytoplasmic immunostaining in the tumor cells of the vast majority of colorectal adenocarcinomas (15). In this study, Tβ4 expression was found even in adenomas with low-grade dysplasia, representing the earliest stage of colorectal tumorigenesis.…”
Section: Discussionmentioning
confidence: 87%
“…Recently, Tβ4 immunoreactivity was detected by our group in the vast majority of colon carcinomas, where it showed a patchy distribution and well-differentiated areas that were significantly more reactive than less-differentiated tumor zones. Moreover, the localization of Tβ4 changed during cancer progression, moving from the cell membrane to the Golgi apparatus (15). …”
Section: Introductionmentioning
confidence: 99%